EVIDENCE FROM CHARCOAL ANALYSIS FOR THE EXTENSIVE EXPLOITATION OF CORK-OAK (QUERCUS SUBER) FOREST IN THE ROMAN IMPERIAL PERIOD: THE VICUS OF THAMUSIDA (NW MOROCCO) - ALLEVATO, Emilia; PECCI, Alessandra; PAPI, Emanuele; Pasquale, Gaetano Di (Proceedings of the Fourth International Meeting of Anthracology, 2013)
This work shows the preliminary results of the study of charcoal collected in the vicus of Thamusida – Sidi Ali ben Ahmed (Morocco), in the Roman province of Mauretania Tingitana. The charcoal assemblage gives information on the woody flora and the wood usage during a period from the second half of the 1st cent. AD to the 3rd cent. AD, during the Roman occupation of the site. Data suggest the presence of a Quercus suber forest in the close surrounding of the site, with larger extension with respect to the present-day Mamora forest. The presence of Vitis vinifera and Olea europaea in the agrarian landscape was also detected. The presence within the charcoal assemblages of Castanea sativa it is worth to note since its presence in the wild vegetation in the surrounding of the site is rather improbable
The following values have no corresponding Zotero field: periodical: Proceedings of the Fourth International Meeting of Anthracology issue: September 2008
Keywords: CHARCOAL ANALYSIS; Firewood; Mamora forest; Roman imperial period; Timber